Seleksi dan Pengujian Bakteri Biokontrol terhadap Cendawan Patogen Fusarium sp. yang Diisolasi dari Buah Tomat (Solanum Lycopersicum L.): Selection and Testing of Biocontrol Bacteria against Pathogenic Fungi Fusarium sp. Isolated from Tomato Fruits (Solanum lycopersicum L.) - Ayni, Qurrotu; Mubarik, Nisa Rachmania; Sudirman, Lisdar I (Jurnal Sumberdaya Hayati, 2025)
Fusarium oxysporum is one of the primary pathogens in tomato plants that causes plant wilting. Pathogenic fungi have been controlled by spraying synthetic fungicides. The negative impact of excessive use of synthetic chemicals can be reduced by using biocontrol agents that produce antifungal compounds. Natural pest control efforts use endophytic bacteria and rhizosphere as biocontrol agents for fungal pathogens on tomato plants (Solanum lycopersicum L). This study aims to select and test biocontrol bacteria against pathogenic fungi Fusarium sp. isolated from tomato fruits. Fusarium successfully isolated from tomato fruits which was characterized based on observations of colony and cell morphology. A total of 15 rhizosphere bacterial isolates were tested against Fusarium sp., and 11 bacterial isolates were able to inhibit the growth of the fungus. Isolates TTSG 2.2, TTSG 2.7, TTSG 3.2, TTSG 3.5, TTSG 3.6, and TCS 3.1 had fungal inhibition of 45%. The results of the hemolysin test showed that one isolate, TTSG 3.6 isolate, was negative, which did not form a clear zone around the bacterial streak. Isolate TTSG 3.6 still showed a few brown spots and rotted tomato fruit, so this bacteria needs to be tested for hypersensitivity on tobacco leaves to show its pathogenicity in plants.